Horizontal-to-vertical velocity conversion in the triple jump - Yu, B. (Journal of Sports Sciences, 1999)
The aim of this study was to determine the effects of selected factors on horizontal-to-vertical velocity conversion in the triple jump. An understanding of this conversion is important not only for studies on the techniques of the triple jump, but also for other jumping events. Ten elite jumpers were studied. Three-dimensional kinematic data were collected for at least four complete trials in the same competition for each athlete. The loss in horizontal velocity and the gain in vertical velocity during each support phase were calculated for each trial. The loss in horizontal velocity was found to be a linear function of the gain in vertical velocity. The slope of this linear function, A1, is referred to as the horizontal-to-vertical velocity conversion coefficient. The loss in horizontal velocity increased as the gain in vertical velocity increased. The sensitivity of the loss in horizontal velocity to the gain in vertical velocity increased as the magnitude of A1 increased. Further studies are required on the optimum techniques of the triple jump.